Evaluation of the cefonicid disk test criteria, including disk quality control guidelines. - Barry, A L (1983)
Cefonicid (SKF 75073) is a second-generation cephalosporin which has a spectrum of antimicrobial activity similar to that of cefamandole, but cefoxitin (a cephamycin) and cephalothin have uniquely different spectra of activity. The second-generation cephalosporins tested displayed comparable susceptibility to beta-lactamases and inhibited type I beta-lactamases. Although cefonicid has a longer serum half-life (3 to 4 h) compared with the currently used drugs, the same minimal inhibitory concentration breakpoints separating susceptible and resistant categories were applied to tests with cefonicid, cefamandole, and cephalothin. Regression analysis of the disk diffusion test results confirmed the use of identical zone size breakpoints for 30-micrograms cefonicid, cefamandole, and cephalothin disks: all three produced similar parabolic regression lines. Further analysis of disk test data confirmed the fact that cefonicid and cefamandole disks might be used interchangeably. But for routine tests, cefonicid disks might be preferred in order to minimize the number of very major (false-susceptible) interpretive errors. Suggested cefonicid 30-micrograms disk interpretive criteria are: susceptible, greater than or equal to 18 mm (less than or equal to 8.0 micrograms/ml), and resistant, less than or equal to 14 mm (greater than 16 micrograms/ml). Quality control zone diameter limits were calculated from data obtained in a multilaboratory collaborative study.